Bias Observed in Time-of-Flight Shear Wave Speed Measurements Using Radiation Force of a Focused Ultrasound Beam - Zhao, Heng; Song, Pengfei; Urban, Matthew W.; Kinnick, Randall R.; Yin, Meng; Greenleaf, James F.; Chen, Shigao (Ultrasound in medicine & biology, 2011)
Measurement of shear wave propagation speed has important clinical applications because it is related to tissue stiffness and health state. Shear waves can be generated in tissues by the radiation force of a focused ultrasound beam (push beam). Shear wave speed can be measured by tracking its propagation laterally from the push beam focus using the time-of-flight principle. This study shows that shear wave speed measurements with such methods can be transducer, depth and lateral tracking range dependent. Three homogeneous phantoms with different stiffness were studied using curvilinear and linear array transducer. Shear wave speed measurements were made at different depths, using different aperture sizes for push and at different lateral distance ranges from the push beam. The curvilinear transducer shows a relatively large measurement bias that is depth dependent. The possible causes of the bias and options for correction are discussed. These bias errors must be taken into account to provide accurate and precise time-of-flight shear wave speed measurements for clinical use.